The Russian Labor Market : Moving from Crisis to Recovery - World Bank (Moscow: Izdatelstvo Ves Mir and the World Bank, 2013)
This report suggests measures to help Russia develop a formal, competitive labor market over the medium term. The study addresses four major questions: (1) How well has Russia been able to redress the misallocation of labor inherited from its socialist past? (2) Do wages increasingly reflect market forces? (3) Are labor market institutions consistent with those required in a market economy? (4) How well has Russia been able to reduce explicit protection offered by firms and create an effective safety net? The report addresses each question in a separate chapter and also highlights key issues and policy options in each area. The development of a well functioning labor market will contribute to Russia's ability to integrate with the global economy, particularly as it faces the opportunity and challenges that will come with World Trade Organization accession.